COVERAGE OF THE INTRODUCTION OF LATIN SPELLING FOR THE FIRST TIME IN UZBEKISTAN IN A PERIODICAL PUBLISHING HOUSE (Western European Journal of Historical Events and Social Science, 2024)
This scientific article analyzes the issues of periodic press coverage of the introduction of Latin spelling in the Uzbek SSR in the first half of the 20th century. These was analyzed by reading the basic of newspapers in the period of thought. In the periodic press, it was noted that all decisions and meetings in which the Latin spelling was introduced, and the results of the conference were printed and published.